PERFORMANCE EVALUATION OF TRAYS IN ATMOSPHERIC FRACTIONATION COLUMN WITH SOUTH PALEMBANG DISTRICT (SPD) CRUDE OIL FEED - Achmad Faisal Faputri; Indah Agus Setiorini (Jurnal Cakrawala Ilmiah, 2023)
Distillation's role is to separate the components it separates based on the boiling point of each component to produce the desired product with the principle of evaporation, namely the evaporation of components. In the industrial world the role of fractional distillation is very important. This study aims to design a fractional distillation apparatus, to know the process and performance of the column and the theory of fractionation separation with the role of column support facilities. Using raw material in the form of 10 liters of SPD crude oil, the separation is divided into three fractions. Then the product from the top section is the gasoline fraction with a temperature range of 28 - 165 ¬¬oC, the middle section is the kerosene fraction with a temperature range of 165 - 300 oC, and the bottom part is the diesel fraction with a temperature range of 300 - 350 oC. So it can be concluded that the distillation column is in accordance with the desired calculation of the raw materials used.